Oral hypoglycemic agents in the current treatment of Diabetes Mellitus type 2: Metformin - Garmendia-Lorena , Fausto (2020)
irst, a review on of the pathophisiology of diabetes mellitus type 2 (DM2) is done and then the role of Metformin in the treament of this disease, keeping in mind its mechnism of action, indications, its advantages of no producing hypoglycemia nor weight increase, its effects in the children of women with gestational diabetes, restrictions in patients prone to display lactic acidosis, the medicament presentations, way of dosification and side effects. It is concluded that Metformin is a first-line glucose lowering agent in the treatmen of DM2.